Entre números e saias: a trajetória de mulheres professoras de Ciências Exatas da Universidade Federal do Maranhão - SILVA, Fernanda Vanessa de Jesus da (2020)
Statistics have shown the increasing participation of women in different areas of knowledge and, mainly, in science. Despite this reality, advancement within the career does not happen proportionally to their entry into the sector, and it can be seen in the highest positions that the predominance is male, even in those areas where women are the majority. If women can achieve higher degrees in the areas of human and social, what happens so that the same does not happen in the area of exact ?. In view of this, doubts arise as to whether these disparities are related only to the training of these women, or whether other factors, such as gender, social, cultural and political issues, interfere significantly in order for this to occur. In view of these questions, this research aimed to conduct a study on the path and performance of female teachers in undergraduate courses in the area of Exact and Technologies at the Federal University of Maranhão in order to understand the training process and its educational trajectory. To achieve the objectives of this research, we used life trajectories through oral reporting as a way to understand the sexual division of labor and gender relations in the careers of these women. And for their analysis, we used the analysis of Bardin's speech (2011) and Bourdieu's categories of habitus (1983, 1992, 2011, 2013). In order to better understand the central theme of the study, we started by making a historical survey of pioneer women scientists in their fields of study, from Antiquity to the present times, ending with some Nobel Prize winning women. Subsequently, we showed how the process of access of Brazilian women to formal education was, as well as the laws that aimed to guarantee their permanence. We also brought up a discussion as to why we have so few women in the exact area. For this, we carried out a survey of the oldest teacher and the youngest teacher admitted to the Departments of the Center for Exact and Technological Sciences at UFMA, in which we identified three teachers who fit our research profile in the Electrical Engineering course. We conducted an interview with the three teachers in order to identify the reasons why the teachers chose to follow teaching in Higher Education, in addition to describing the possible facilitating elements and possible obstacles to the exercise of teaching in Higher Education. We finished our work, presenting and making an interlacing of speeches and events in the teachers' lives, based on the discussion brought up earlier. We emphasize the pioneering spirit of these teachers as well as their exemplary professional performance. We highlight the need for further studies with the subjects of the research as exact subjects. We anchor our work in the contributions of Schiebinger (2001), Mcgrayne (1994), Yannoulas (2011), Kergoat (2009), Silva (2017) and Nunes (2006).